The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18203/issn.2454-2156.intjscirep20174620
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone as an adjuvant to bupivacaine in brachial plexus block in upper limb surgery

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Supraclavicular brachial plexus block is widely used for surgery below shoulder joint. Adding adjuvant to local anesthetic drugs enhance the duration of block as well as postoperative analgesia. Dexamethasone very potent glucocorticoid when added to local significantly prolongs the duration of analgesia</span>.</p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…For motor block duration, 23 studies were judged to be at low risk of bias [32, 35, 38, 39, 42, 45, 53, 54, 56, 59, 65, 76, 81, 82, 92–94, 107, 110, 113, 115, 116], 67 studies were at some risk of bias [33, 34, 36, 37, 40, 43, 48, 50–52, 55, 57, 58, 60–62, 67, 68, 70–75, 77–80, 83–91, 95–106, 108, 109, 111, 114, 117–126, 128–131] and 3 studies were at high risk of bias [41, 63, 127]. The provision of inadequate detail about randomisation and allocation concealment was the most common reason for downgrading the rating, followed by concerns relating to outcome measurement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For motor block duration, 23 studies were judged to be at low risk of bias [32, 35, 38, 39, 42, 45, 53, 54, 56, 59, 65, 76, 81, 82, 92–94, 107, 110, 113, 115, 116], 67 studies were at some risk of bias [33, 34, 36, 37, 40, 43, 48, 50–52, 55, 57, 58, 60–62, 67, 68, 70–75, 77–80, 83–91, 95–106, 108, 109, 111, 114, 117–126, 128–131] and 3 studies were at high risk of bias [41, 63, 127]. The provision of inadequate detail about randomisation and allocation concealment was the most common reason for downgrading the rating, followed by concerns relating to outcome measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, these arms yielded estimates from indirect comparisons only. Ninety‐three trials with 5668 patients examined motor block duration [32–43, 45, 48, 50–63, 65, 67, 68, 70–111, 113–131] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Engineer et al . [ 12 ] found that dexamethasone, when added to bupivacaine, increased the duration of sensory and motor blocks and duration of effective analgesia. The duration of analgesia was more in this study compared to our study, probably due to the use of higher volume of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%